EVALUASI EFEKTIFITAS SISTEM PENGANGKUTAN DAN PENGELOLAAN SAMPAH DI TPA SARIMUKTI KOTA BANDUNG - Rian Alfian; Arlina Phelia (JICE (Journal of Infrastructural in Civil Engineering), 2021)
The large population and the diversity of activities in big cities in Indonesia have resulted in the emergence of common problems in urban infrastructure services, such as solid waste problems. One of them is the city of Bandung which has the highest landfill load, which is 3.55 m3 (BPLHD, 2008). According to data from PD Kebersihan Bandung City, that waste services only cover 62.73% of the total waste generation. Currently, waste in the city of Bandung is disposed of at the Sarimukti TPA, which is located in Cipatat District, West Bandung Regency. This location and the city of Bandung is relatively far, which is about 45 km from the center of Bandung. The results of the evaluation transport trucks from TPS to TPA Sarimukti at 1 ritation obtained a total time of 10 hours, in the waste collection system only exist one driver who works day and night. The potential gas from CO2 and CH4 landfills to cause a greenhouse effect, it is necessary to capture gas. The IPL configuration, TPA sarimukti consists of an Anaerobic Pond, Aerobic Pool, Sedimentation Pond and Sanitation Pool. However, the parameters for COD, BOD, TDS, free ammonia, and H2S have not met the quality standard. The treatment efficiency is low for COD of only 20% due to the design depth that does not meet the design criteria, the number of aerators is insufficient or the aerators are not started according to the requirements so that the oxygen supply in the aerobic pond is reduced.